COMMUNICATIVE LANGUAGE TEACHING (CLT) AND CLASSROOM INTERACTION: IMPLICATION TO THE FOREIGN LANGUAGE LEARNING AND TEACHING - Gabriel Fredi Da’ar (Unika Santu Paulus Ruteng, 2016)
Communicative Language Teaching (CLT) and Classroom Interaction: Implication to the Foreign Language Learning and Teaching. Language learning aims to gain competence in the language studied both language skills (reading, writing, listening and speaking) and the components of language (sentence patterns, vocabulary and pronunciation). Some ways can be employed to achieve the goals such as independent learning and guided one. In language learning, several approaches are applicable, one of which is Communicative Language Teaching (CLT). Teachers apply this approach with the aim that students have enough time to negotiate and manipulate real situations into the classroom through dialogue, discussion, story-telling, game, roleplay, and debate. Through these activities the learners get a lot of input from the community of learning